Analisis Implementasi Strategi Promosi Produk Pada PT. Indomarco Prismatama Indonesia (Toko Indomaret Telukjambe 58) - M, Mutiara; Mulyadi, Dedi; S, Sungkono (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Indomaret shop Telukjambe 58 experienced a decline in sales of promotion-focused products, causing daily sales to fall. The researcher was tasked with helping the company analyze the strategies that must be implemented to increase sales of promotion-focused products so that later daily sales would increase. With this research, it is certain that researchers can help companies implement strategies that must be carried out in order to increase sales of promotion-focused products. The basic solution that must be implemented at the Indomaret Telukjambe 58 Store in order to increase sales of promotion-focused products and increase the store's daily sales is the participation of all levels of employees concerned in the store in the consistent offering of promotional-focused products to consumers who shop, and the availability of good infrastructure. supports the implementation of ongoing promotional strategies to make it easier for consumers to see what products are currently the focus of promotional products.